The Effect of Silver Nanoparticles Produced from Extract of Medicinal Plant (Kelussia) on Kidney Function Tests - Nezam Armand; Hassan Morovvati; Yaser Azizi (Fasa University of Medical Sciences, 2024)
Background & Objectives: Kelussia odoratissima is involved in the treatment of kidney stones, irritation of the urinary tract and kidney and bladder cleansing. It is useful for gout patients and is used to treat kidney and ureteral stones. The aim of this study was to investigate the effect of Kelussia odoratissima on renal function tests in male rats. Materials & Methods: In this study, 20 rats were randomly divided into one control group and three treatment groups (n=5 per group). The treatment groups received a 40, 80, and 120 mg/kg silver nanoparticles produced by the extracts of Kelussia, orally once a day for 6 days. After taking a blood sample, a kidney function test was performed. SPSS software version 21 was used for data collection, and the results were presented as mean and standard deviation (mean±SEM). Results: Oral administration of silver nanoparticles produced by Kelussia extracts at 80 mg/kg dose significantly reduced bilirubin and urea compared to the control group (P<0.05). The 120 mg/kg dose also significantly reduced urea compared to the control group (P<0.05). There was no significant effect on total protein, albumin and urea. Conclusion: Silver nanoparticles produced by the Kelussia extracts did not show any negative effect on kidney function, but had some positive effect on waste removal.